CHARGE syndrome: A review. (19th February 2014) - Hsu, Peter; Ma, Alan; Wilson, Meredith; Williams, George; Curotta, John; Munns, Craig F; Mehr, Sam
Abstract CHARGE syndrome is a complex genetic syndrome, owing to the wide range of tissues/systems affected by mutations in the CHD7 gene. In this review, we discuss the diagnosis, clinical features and management of CHARGE syndrome.